Zirconocene catalyzed diastereoselective carbometalation of cyclobutenes. Issue 1 (30th August 2016) - Roy, Sudipta Raha; Eijsberg, Hendrik; Bruffaerts, Jeffrey; Marek, Ilan
Abstract : We functionalize cyclobutene species into polysubstituted metalated cyclobutanes through the Dzhemilev reaction. Abstract : The regio- and diastereoselective zirconocene-catalyzed carbomagnesiation of cyclobutenes is herein reported to afford configurationally stable cyclobutylmagnesium species that could subsequently react with a large variety of electrophiles to give polysubstituted cyclobutane species as a single diastereoisomer.